A Neutrosophic Approach to Robust Web Security: Mitigating XSS Attacks - A. A. Salama; El-Said F. Aboelfotoh; Hazem M. El-Bakry; Hazem M. El-Bakry; Ahmed K. Essa; Ramiz Sabbagh; Doaa S. El-Morshedy (Neutrosophic Sets and Systems)
Cross-Site Scripting (XSS) is one of the most grievous vulnerabilities-a pitfall through which web applications are affected. These types of attacks are complex, and the available threat landscape is always changing, making it hard for conventional security tools to effectively detect or prevent these types of attacks. We present here an approach that detects and prevents XSS attacks on Web pages. Since Neutrosophism works with different kinds of data, it aims at the validity degree of the attack. This way the system understands the different types of attacks and allows the system to act more effectively. Our system combines (1) static analysis-to look into the code behind the website-with (2) dynamic analysis-to watch the website in action. Moreover, a proactive defense watches youruser behavior and scrubs every input/output.XSS, Cross-Site Scripting, Neutrosophic Logic, Web Security, Static Analysis, Dynamic